2008
DOI: 10.1002/dmrr.779
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1 activity, but not fibrinogen or von Willebrand factor, is inversely related to LDL particle size in type 2 diabetes

Abstract: PAI-1 activity levels, in contrast to fibrinogen and vWF:Ag, seem to be related to the small LDL phenotype in patients with type 2 diabetes. However, this relationship was not independent of insulin resistance or triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…This is in contrast with the negative correlation observed with plasma PAI-1 levels in the present study and to what we might have expected [29][30][31]. In accordance with our observations, Lindeman et al [30] found an inverse relationship between abdominal subcutaneous and visceral AT PAI-1 mRNA levels and BMI values.…”
Section: Discussionsupporting
confidence: 77%
“…This is in contrast with the negative correlation observed with plasma PAI-1 levels in the present study and to what we might have expected [29][30][31]. In accordance with our observations, Lindeman et al [30] found an inverse relationship between abdominal subcutaneous and visceral AT PAI-1 mRNA levels and BMI values.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, increased basal PAI-1 level significantly correlated with HDL-chol, but only in T2D patients. In accordance with our results, Mertens et al demonstrated that PAI-1 activity was significantly related to HDL-chol in T2D patients free of CAD [ 41 ]. They also pointed out a strong relationship between PAI-1 and LDL peak particle diameter but not with LDL cholesterol levels.…”
Section: Discussionsupporting
confidence: 93%
“…These authors confirmed a positive correlation between PAI-1 and TG. PAI-1 levels correlated also with total cholesterol but not with LDL-C or HDL-C. A significant association between PAI-1 activity (in contrast to fibrinogen and vWF) and LDL particle size in type 2 diabetes was detected recently [41]. The relationship was not independent of insulin resistance or triglycerides.…”
Section: Discussionmentioning
confidence: 91%